Achieving Sustainability in the Assembly of Modified Nucleosides Using Green Solvents - Kudalkar, Mahadev V.; Patel, Manisha A.; Sanghvi, Yogesh S.; Kapdi, Anant R. (Sustainability & Circularity NOW, 2025)
Chemical modifications of nucleosides have been a topic of special interest for researchers, given the plethora of applications these structural motifs have been able to demonstrate. For decades, such modifications have been performed in conventional volatile organic solvents that have severe environmental implications. A recent trend suggests a shift in the strategy, with many researchers using sustainable and green solvents such as ionic liquids (ILs), H2O, deep eutectic solvents (DES), and 2-MeTHF for performing key transformations on the nucleoside’s structural motif. This review critically analyzes examples of nucleoside functionalization carried out in different sustainable solvents and also helps to assess the feasibility of such solvent choices for further applications.
Keywords: Nucleosides; Sustainable solvents; Green solvents; Chemical functionalization; Deep eutectic solvents; Ionic liquids; Suzuki–Miyaura cross-coupling; Amination